2014
DOI: 10.1186/1746-6148-10-29
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil and macrophage apoptosis in bronchoalveolar lavage fluid from healthy horses and horses with recurrent airway obstruction (RAO)

Abstract: BackgroundDysregulation of apoptosis has been implicated in a range of diseases including tumors, neurodegenerative and autoimmine diseases, as well as allergic asthma and chronic obstructive pulmonary disease (COPD) in humans. Although it has a different pathophysiology, delayed apoptosis of various inflammatory cells may play a pivotal role in the development of recurrent airway obstruction (RAO) in horses. Reduction of inflammatory cell apoptosis or a dysregulation of this process could lead to chronic infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Lack of the above mentioned data creates difficulties in assessing and comparing the results with those of other authors. In humans, many insights have been made into the pathogenesis of diseases such as rheumatoid arthritis and glomerulonephritis, using the analysis of the levels of circulating immune complexes levels (Nowak-Łoś et al 2013, Navolotskaya 2014, Wener 2014. The incidence of circulating immune complexes has been ascertained for many disease conditions (Haymen 1990, Pandey 2013, Maheswari et al 2014) and the level of circulating immune complexes has been correlated with the activity of certain diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lack of the above mentioned data creates difficulties in assessing and comparing the results with those of other authors. In humans, many insights have been made into the pathogenesis of diseases such as rheumatoid arthritis and glomerulonephritis, using the analysis of the levels of circulating immune complexes levels (Nowak-Łoś et al 2013, Navolotskaya 2014, Wener 2014. The incidence of circulating immune complexes has been ascertained for many disease conditions (Haymen 1990, Pandey 2013, Maheswari et al 2014) and the level of circulating immune complexes has been correlated with the activity of certain diseases.…”
Section: Discussionmentioning
confidence: 99%
“…An endoscopy and BAL procedure was performed using methods previously described (Niedzwiedz et al 2014). The amount of the recovered fluid was recorded and BALF for each individual horse was pooled in a sterile specimen cup, placed on ice and processed within 2h after collection.…”
Section: Collection and Cytologic Evaluation Of Balfmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory cell populations in the lung represent a balance between cellular recruitment, via airway epithelial cell and macrophage‐derived chemotactic cytokines, and removal, via apoptosis and phagocyte‐mediated clearance. Lung granulocytes (neutrophils and macrophages) in horses with RAO exhibit altered apoptosis, which together with increased activity of transcription factors such as nuclear factor‐κB (NF‐κB) and activator protein‐1 (AP‐1) might contribute to the maintenance of neutrophilic inflammation in horses treated with glucocorticoids and maintained in an allergenic environment . Whilst no age‐related trends in BALF cytological profiles in horses with IAD or RAO have been reported, there is an age‐associated increase in mRNA expression of IFN‐γ producing lymphocytes in stimulated BAL cells .…”
Section: Late‐onset Asthmamentioning
confidence: 99%
“…Only one study reported an increased expression of apoptotic related proteins in adipose and hepatic tissue of horses with equine metabolic syndrome [64]. However, other reports have studied the effects of different diseases, such as asthma [65], colitis and lipopolysaccharide infusion [66,67], upon neutrophil apoptosis. Interestingly, delayed neutrophil apoptotic rates have been reported in the studies mentioned above.…”
Section: Discussionmentioning
confidence: 99%